Staurosporine Induces Filamentation in the Human Fungal Pathogen Candida albicans via Signaling through Cyr1 and Protein Kinase A - Jinglin L. Xie (American Society for Microbiology, 2017)
ABSTRACT Protein kinases are key regulators of signal transduction pathways that participate in diverse cellular processes. In fungal pathogens, kinases regulate signaling pathways that govern drug resistance, stress adaptation, and pathogenesis. The impact of kinases on the fungal regulatory circuitry has recently garnered considerable attention in the opportunistic fungal pathogen Candida albicans, which is a leading cause of human morbidity and mortality. Complex regulatory circuitry governs the C. albicans morphogenetic transition between yeast and filamentous growth, which is a key virulence trait. Here, we report that staurosporine, a promiscuous kinase inhibitor that abrogates fungal drug resistance, also influences C. albicans morphogenesis by inducing filamentation in the absence of any other inducing cue. We further establish that staurosporine exerts its effect via the adenylyl cyclase Cyr1 and the cyclic AMP (cAMP)-dependent protein kinase A (PKA). Strikingly, filamentation induced by staurosporine does not require the known upstream regulators of Cyr1, Ras1 or Pkc1, or effectors downstream of PKA, including Efg1. We further demonstrate that Cyr1 is capable of activating PKA to enable filamentation in response to staurosporine through a mechanism that does not require degradation of the transcriptional repressor Nrg1. We establish that staurosporine-induced filamentation is accompanied by a defect in septin ring formation, implicating cell cycle kinases as potential staurosporine targets underpinning this cellular response. Thus, we establish staurosporine as a chemical probe to elucidate the architecture of cellular signaling governing fungal morphogenesis and highlight the existence of novel circuitry through which the Cyr1 and PKA govern a key virulence trait. IMPORTANCE The impact of fungal pathogens on human health is devastating. One of the most pervasive fungal pathogens is Candida albicans, which kills ~40% of people suffering from bloodstream infections. Treatment of these infections is extremely difficult, as fungi are closely related to humans, and there are limited drugs that kill the fungus without host toxicity. The capacity of C. albicans to transition between yeast and filamentous forms is a key virulence trait. Thus, understanding the genetic pathways that regulate morphogenesis could provide novel therapeutic targets to treat C. albicans infections. Here, we establish the small molecule staurosporine as an inducer of filamentous growth. We unveil distinct regulatory circuitry required for staurosporine-induced filamentation that appears to be unique to this filament-inducing cue. Thus, this work highlights the fact that small molecules, such as staurosporine, can improve our understanding of the pathways required for key virulence programs, which may lead to the development of novel therapeutics.